Analisis Hubungan Bauran Pemasaran dengan Nilai Penjualan Pembibitan Jati (Tectona grandis) di CV Mitra Perapi Desa Anaiwoi Kecamatan Tanggetada Kabupaten Kolaka - Helviani Helviani (AGRIMOR, 2021)
This study aims to determine how the correlation of the mix marketing (product, price, place, and promotion) with the sales value of teak (Tectona grandis) at CV Mitra Perapi, Anaiwoi Village, Tanggetada District, Kolaka Regency. Respondents in this study were managers and all workers or employees of CV Mitra Perapi, totaling 30 people. The main variables in this study are marketing mix (product, price, place, and promotion) and sales value. The analytical tool used in this study is the Spearman correlation analysis. The results showed that the range of the highest Spearman correlation coefficient was in the price marketing mix, which was 0.655 which meant that the relationship between the marketing mix (price) and the sale value of teak seedlings had a strong correlation. Meanwhile, the lowest spearman correlation coefficient is in the promotional marketing mix, which is 0.136, which means that the correlation between the marketing mix (promotion) and the sale value of teak seeds does not show a significant correlation because the resulting correlation coefficient value shows a very low or weak correlation.